Lithium-coupled electron transfer reactions of nano-confined WOx within Zr-based metal–organic framework - Ghuffar, Hafsa Abdul; Noh, Hyunho (Frontiers in Chemistry, 2024)
Interfacial charge transfer reactions involving cations and electrons are fundamental to (photo/electro) catalysis, energy storage, and beyond. Lithium-coupled electron transfer (LCET) at the electrode-electrolyte interfaces of lithium-ion batteries (LIBs) is a preeminent example to highlight the importance of charge transfer in modern-day society. The thermodynamics of LCET reactions define the minimal energy for charge/discharge of LIBs, and yet, these parameters are rarely available in the literature. Here, we demonstrate the successful incorporation of tungsten oxides (WOx) within a chemically stable Zr-based metal−organic framework (MOF), MOF-808. Cyclic voltammograms (CVs) of the composite, WOx@MOF-808, in Li+-containing acetonitrile (MeCN)-based electrolytes showed an irreversible, cathodic Faradaic feature that shifted in a Nernstian fashion with respect to the Li+ concentration, i.e., ∼59 mV/log [(Li+)]. The Nernstian dependence established 1:1 stoichiometry of Li+ and e−. Using the standard redox potential of Li+/0, the apparent free energy of lithiation of WOx@MOF-808 (ΔGapp,Li) was calculated to be −36 ± 1 kcal mol−1. ΔGapp,Li is an intrinsic parameter of WOx@MOF-808, and thus by deriving the similar reaction free energies of other metal oxides, their direct comparisons can be achieved. Implications of the reported measurements will be further contrasted to proton-coupled electron transfer (PCET) reactions on metal oxides.